Preparation of Small RNAs Using Rolling Circle Transcription and Site-Specific RNA Disconnection - Xingyu Wang; Can Li; Xiaomeng Gao; Jing Wang; Xingguo Liang (Elsevier, 2015)
A facile and robust RNA preparation protocol was developed by combining rolling circle transcription (RCT) with RNA cleavage by RNase H. Circular DNA with a complementary sequence was used as the template for promoter-free transcription. With the aid of a 2'-O-methylated DNA, the RCT-generated tandem repeats of the desired RNA sequence were disconnected at the exact end-to-end position to harvest the desired RNA oligomers. Compared with the template DNA, more than 4 × 103 times the amount of small RNA products were obtained when modest cleavage was carried out during transcription. Large amounts of RNA oligomers could easily be obtained by simply increasing the reaction volume.